(untitled) (Acta Scientiarum. Biological Sciences, 2021)
The use of genotypes more adapted to climatic conditions can contribute to increase the yield of onion producers. The goal of this study was to evaluate the agronomic performance of 15 onion genotypes in the soil and climatic conditions of Guarapuava, state of Paraná. The study was conducted in the experimental area of Horticulture, Cedeteg campus, Universidade Estadual do Centro-Oeste (UNICENTRO), Guarapuava, state of Paraná, Brazil, from July to November 2018. The experimental design used was randomized blocks, with four replications, and the treatments consisted of four commercial cultivars Optima F1, Bella Dura, Sirius F1, Soberana F1 and eleven experimental genotypes N1, N2, N3, N4, N5, N6, N7, N8, N9, AF4241 and AF4243. Biometric characteristics of the plants, production components and early flowering were evaluated. Plants presented between 6 and 9 leaves, in which N1, N3, N4 and N6 had less than 7 leaves, differing statistically from the others. The cultivar Optima F1 and the genotypes N2, N3, N5, N6, N7 and N8 presented the tallest plants, with 66.1 to 76.0 cm. The pseudostem diameter did not differ significantly between genotypes, showing values between 15.2 and 20.4 mm. Total productivity was higher in genotypes N2, N6, N5, N4, N3, N7 with values from 43.6 to 50.3 t ha-1. The highest average bulb mass was found in N2, N4, N6, Sirius F1, Optima F1 and Soberana F1, with 74.2 to 91.1 g bulb-1. Regarding the commercial classification, the genotypes N2, N4, N5, N6 and the cultivars Sirius F1 and Soberana F1 presented more than 50% bulbs of classes 3+3C+4. Early flowering did not occur in any of the analyzed genotypes. The use of cultivars with high productive performance and adapted to climatic conditions, when handled properly, can result in greater yield and quality of bulbs.